Travessia - memórias, poéticas e políticas de um teatro negro: um estudo sobre a trajetória do grupo Travessia, Ribeirão Preto/SP - Silva, Washington de Paula e (2024)
This study explores the artistic and political trajectory of the Grupo de Cultura e Arte Negra Travessia, which operated in Ribeirão Preto between the 1970s and 2000s. The group transformed several spaces into black territories through performances, shows, and other actions, always aligned with the cultural traditions of the African diaspora in Brazil and the black political movement. We promote a critical analysis of our theatrical history, questioning the absence of black people and the racist perspective employed in portraying them. We explore the conceptualization of the term "black theater" and the historical milestones that inaugurated black theater in Brazil as an artistic-political movement. As we delve into the period of the founding of the Travessia group, we emphasize the relationship between the group and a large network of black organizations in the state of São Paulo, and how these were fundamental to its consolidation in the theatrical scene. We address the creative procedures of their stage productions and political activities, together with other black organizations, mainly in the sociopolitical context of Ribeirão Preto and the state of São Paulo at the time. However, we focus on the relationship and closeness of the members with the group, the organizational structure of rehearsals, stage methodologies, and cultural production. In particular, we highlight the trajectory of Pedro Paulo, as director, actor, and playwright of Travessia, a self-taught artist who, through theater, poetry, dance, and popular Afro-Brazilian expressions, sought in his artistic, cultural, and political creation, the construction of other narratives and positive references for the black population. Pedro Paulo was the main pillar that supported the Travessia group for more than two decades, devoting himself devotedly to theater and the black struggle. Analytically, we recorded the artistic and political production of the group, whose productions were based on Afro-Brazilian culture, unfolding in several actions, including the organization of black culture festivals, performances, shows, the creation of a newspaper and incursions into the field of art education, all carried out at different times throughout almost three decades of existence. We conclude that it is still necessary to reflect on the processes of invisibility of black artists in our history. By portraying the history of Travessia, we act within fissures in the racist structures that still promote the exclusion of black people, moving against this process. Despite all the barriers imposed by being a black theater group, Travessia existed and resisted for decades, acting as a platform for the valorization of black people. Finally, we understand the importance of claiming authorship of the black history of Brazilian theater, which includes black artists who have not been recognized as subjects in official history.